Analisis Daya Dukung Pondasi Tiang Pancang Menggunakan Data Laboratorium dengan Metode Meyerhoff, Alpha, Beta, Lamda (Studi Kasus: Proyek Pembangunan Gedung Bess Mansion Jemursari Surabaya) - Putra, Ferdiansyah Mas; Fatmawati, Laily Endah; Firmansyah, Yerry Kahidatu (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to analyze the bearing capacity of pile foundations in the Bess Mansion Building Project in Jemursari, Surabaya, using the Meyerhof, Alpha, Beta, and Lamda methods. The analysis is based on laboratory data reflecting actual soil conditions at the site. The calculation methods include evaluations of end and shaft bearing capacities, overburden stress, and adhesion or friction coefficients. Results indicate that the Alpha method yields the highest allowable bearing capacity at 2754.13 tons, followed by the Beta method at 2290,95 tons, and the Lambda method at 501.25 tons. All results demonstrate safe capacities to support the planned load of 300 tons. In conclusion, the Lamda method is the most effective for this case study. This research provides recommendations for selecting appropriate bearing capacity estimation methods tailored to soil conditions to ensure structural safety and implementation efficiency.